2019
DOI: 10.1186/s12862-019-1349-8
|View full text |Cite
|
Sign up to set email alerts
|

Morphological diversification of biomechanical traits: mustelid locomotor specializations and the macroevolution of long bone cross-sectional morphology

Abstract: BackgroundMorphological diversity of limb bone lengths, diameters, and proportions in mammals is known to vary strongly with locomotor habit. It remains less well known how different locomotor habits are correlated with cross-sectional traits of the limb skeleton, such as cross-sectional area (CSA), second moments of area (SMA), and section modulus (MOD) and whether these traits have evolved adaptively. CSA and SMA represent the bone’s resistance to axial compression and bending, respectively, whereas MOD repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 96 publications
4
41
0
1
Order By: Relevance
“…Research performed on primates' long bone CSP indicated sturdier bones for arboreal species when compared to terrestrial ones (Kimura, 1991(Kimura, , 1995 and more robust femurs in non-anthropoid primates that tend to leap compared to those that avoid leaping (Demes & Jungers, 1993). Kilbourne and Hutchinson (2019) found less robust forelimb long bones in scansorial mustelids when compared to generalized, natatorial, and fossorial mustelids. In Sciuromorpha, we expected differences in CSP among all three lifestyle categories, with decreasing mean values from aerial to arboreal and finally fossorial species.…”
Section: Influence Of Locomotor Ecology On Cspmentioning
confidence: 99%
See 3 more Smart Citations
“…Research performed on primates' long bone CSP indicated sturdier bones for arboreal species when compared to terrestrial ones (Kimura, 1991(Kimura, , 1995 and more robust femurs in non-anthropoid primates that tend to leap compared to those that avoid leaping (Demes & Jungers, 1993). Kilbourne and Hutchinson (2019) found less robust forelimb long bones in scansorial mustelids when compared to generalized, natatorial, and fossorial mustelids. In Sciuromorpha, we expected differences in CSP among all three lifestyle categories, with decreasing mean values from aerial to arboreal and finally fossorial species.…”
Section: Influence Of Locomotor Ecology On Cspmentioning
confidence: 99%
“…Here, we aimed to gain insight into the evolution of adaptations of the cross‐sectional properties (CSP) of the sciuromorph femur. For this purpose, we quantified them in 5% increments along the length of the bone following the approach of Doube et al (, ) and Kilbourne and Hutchinson (). The three CSP analyzed here are proxies of different uni‐ or multidimensional forces the bones experience (Ruff & Runestad, ; Schaffler, Burr, Jungers, & Ruff, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mustelidae are a carnivoran lineage exhibiting a diversity of locomotor habits. Specifically among mustelids, three main locomotor specializations can be defined [7,8]: badgers are fossorial, featuring specialized digging skills; martens are scansorial, as they are preponderantly found climbing; otters are natatorial, being skilful swimmers. In addition to these three specializations, weasels exhibit a more generalized locomotor habit.…”
Section: Introductionmentioning
confidence: 99%